Suicídio na adolescência: revisão de literatura - Souza, Ana Claudia Gondin [UNESP]; Barbosa, Guilherme Correa [UNESP]; Moreno, Vânia [UNESP] (My University, 2015)
The present study is about an investigation that used as methodological strategy the systematic review. A literature review was carried out in the database of the Scientific Electronic Library Online. Eight articles, on Suicide in Adolescence, were selected to evaluate the contribution of scientific research published in national periodicals during the period 2001 to 2014. From the data analysis, two categories emerged: adolescent profile which tried suicide and socio-cultural influence.

Trata-se de uma investigação que utilizou como estratégia metodológica a revisão sistemática. Foi realizado um le- vantamento bibliográfico na base de dados da Scientific Eletronic Library Online. Oito artigos foram selecionados a partir da questão que permeou o estudo, qual seja, conhe- cer a contribuição das investigações científicas publicadas nos periódicos nacionais no período de 2001 a 2014 sobre suicídio na adolescência. A partir da análise de dados emergiram duas categorias: Perfil do adolescente com tentativa de suicídio e a influência sociocultural.
Suicide during adolescence: literature review
Keywords: Suicide; Adolescence; Adolescent; Suicídio; Adolescência; Adolescente